2021
DOI: 10.1007/s00380-021-01783-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on phase 2 cardiac rehabilitation patients in Japan

Abstract: This study aimed to clarify the effects of the interruption of cardiac rehabilitation (CR) and refraining from going outside due to the COVID-19 pandemic on hemodynamic response and rating of perceived exertion (RPE) during exercise including differences by age in phase 2 CR outpatients. Among 76 outpatients participating in consecutive phase 2 CR in both periods from March to April and June to July 2020, which were before and after CR interruption, respectively, at Sanda City Hospital were enrolled. The inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Therefore, we tend to believe that the clinical relevance of diagnosed events was comparable among phases, and that patients may have experienced more frequent episodes of true HF decompensation. Indeed, the detrimental effects of the lockdown in patients with cardiovascular diseases have recently been demonstrated [ 23 ]. Our findings seem to disagree with the observations of a recent work that suggested potential beneficial effects of the lockdown in ICD patients for the reduction in real-life stressors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we tend to believe that the clinical relevance of diagnosed events was comparable among phases, and that patients may have experienced more frequent episodes of true HF decompensation. Indeed, the detrimental effects of the lockdown in patients with cardiovascular diseases have recently been demonstrated [ 23 ]. Our findings seem to disagree with the observations of a recent work that suggested potential beneficial effects of the lockdown in ICD patients for the reduction in real-life stressors [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the onset of COVID-19 lockdown restrictions were reported to reduce activity levels, in the form of step counts, by 16% in a population of heart failure patients [ 38 ]. Furthermore, research from CR participants in Japan revealed that COVID-19 related interruptions in CR practice were negatively associated with both activity levels and hemodynamic response, relative perceived exertion during exercise as well as body weight [ 39 ]. Older patients in particular (≥ 75 years), were also at greater risk of frailty [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, research from CR participants in Japan revealed that COVID-19 related interruptions in CR practice were negatively associated with both activity levels and hemodynamic response, relative perceived exertion during exercise as well as body weight [ 39 ]. Older patients in particular (≥ 75 years), were also at greater risk of frailty [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we could not evaluate the impact on outpatient outcomes. Interruption of outpatient programs could adversely impact patients, [34][35][36] and further studies are needed to confirm this assumption. Subsequently, the results of the present study were based on nationwide data from multiple centers in Japan.…”
Section: Discussionmentioning
confidence: 99%